The Jewish Study Bible - Berlin, Adele; Brettler, Marc Zvi; Jewish Publication Society (Oxford : New York, New York : Oxford University Press, 2014)
"The Jewish Study Bible combines the entire Hebrew Bible--in the celebrated Jewish Publication Society TANAKH Translation--with explanatory notes, introductory materials, and essays by leading biblical scholars on virtually every aspect of the text, the world in which it was written, its interpretation, and its role in Jewish life. The quality of scholarship, easy-to-navigate format, and vibrant supplementary features bring the ancient text to life"--Publisher's Web site.
Torah -- Nevi'im -- Kethuvim -- Essays. Jewish interpretation of the Bible ; Biblical ideas and institutions ; The Bible in Jewish life ; Backgrounds for reading the Bible ; The Hebrew Bible in other scriptures.
Text in English.
"Jewish Publication Society Tanakh translation."
Previous edition published: 2004.
Includes preface to the 1985 JPS edition, published under title: Tanakh : a new translation of the Holy Scriptures according to the traditional Hebrew text.
Includes: The new Oxford Bible maps, Jewish Study Bible / prepared by Oxford cartographers and based on the Oxford Bible atlas (14 pages at end of volume).
Includes bibliographical references and indexes.
Keywords: Bible -- Commentaries; Bible -- Versions, Jewish